The roles of toll-like receptor 4, CD33, CD68, CD69, or CD147/EMMPRIN for monocyte activation by the DAMP S100A8/S100A9 - Möller, Alexander; Jauch-Speer, Saskia-Larissa; Gandhi, Shrey; Vogl, Thomas; Roth, Johannes; Fehler, Olesja (Frontiers in Immunology, 2023)
The S100A8/A9 heterocomplex is an abundant damage-associated molecular pattern and mainly expressed by monocytes, inflammatory activated keratinocytes and neutrophilic granulocytes. The heterocomplex as well as the heterotetramer are involved in a variety of diseases and tumorous processes. However, their detailed mode of action and especially which receptors are involved hereby remains to be fully revealed. Several cell surface receptors are reported to interact with S100A8 and/or S100A9, the best studied being the pattern recognition receptor TLR4. RAGE, CD33, CD68, CD69, and CD147, all of them are involved as receptors in various inflammatory processes, are also among these putative binding partners for S100A8 and S100A9. Interactions between S100 proteins and these receptors described so far come from a wide variety of cell culture systems but their biological relevance in vivo for the inflammatory response of myeloid immune cells is not yet clear. In this study, we compared the effect of CRISPR/Cas9 mediated targeted deletion of CD33, CD68, CD69, and CD147 in ER-Hoxb8 monocytes on S100A8 or S100A9 induced cytokine release with TLR4 knockout monocytes. Whereas deletion of TLR4 abolished the S100-induced inflammatory response in monocyte stimulation experiments with both S100A8 and S100A9, knockouts of CD33, CD68, CD69, or CD147 revealed no effect on the cytokine response in monocytes. Thus, TLR4 is the dominant receptor for S100-triggered inflammatory activation of monocytes.